2021
DOI: 10.1177/08903344211026565
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Experiences During the COVID-19 Lockdown in the United Kingdom: An Exploratory Study Into Maternal Opinions and Emotional States

Abstract: Background The COVID-19 pandemic has hugely impacted upon people’s psychological and physical wellbeing; however, the effects of the COVID-19 lockdown on mothers of young children, with particular regard to breastfeeding, are unknown. Research Aims To explore: (1) Sources of advice and support available to breastfeeding mothers during and prior to the COVID-19 lockdown; (2) Mothers’ opinions on statements and recommendations made by the World Health Organization on the importance of breastfeeding and breastfee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 60 publications
3
21
0
10
Order By: Relevance
“…It was determined that the level of knowledge about breast milk, the level of knowledge about COVID-19 disease and sociodemographic characteristics were not effective on the breastfeeding behavior. In Costantini's study from United Kingdom which is very similar to ours, emotional states of breastfeeding mothers were evaluated during COVID-19 pandemic via Generalized Anxiety Disorder Questionnaire and found that mothers with more than one child showed higher negative emotional states, especially anxiety symptoms ( 16 ). We used state and trait anxiety questionnaire and aimed to understand whether state anxiety status is associated with pandemic.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It was determined that the level of knowledge about breast milk, the level of knowledge about COVID-19 disease and sociodemographic characteristics were not effective on the breastfeeding behavior. In Costantini's study from United Kingdom which is very similar to ours, emotional states of breastfeeding mothers were evaluated during COVID-19 pandemic via Generalized Anxiety Disorder Questionnaire and found that mothers with more than one child showed higher negative emotional states, especially anxiety symptoms ( 16 ). We used state and trait anxiety questionnaire and aimed to understand whether state anxiety status is associated with pandemic.…”
Section: Discussionsupporting
confidence: 62%
“…However, this recommendation does not seem to be used practically in our study. Findings in Costantini's and our studies show that the age of the breastfed child and having more than one child increase the anxiety in mothers, especially during the pandemic period ( 16 ). 1 , 2…”
Section: Discussionsupporting
confidence: 52%
“…A study carried out in April 2020 during a UK lockdown period identified that infant feeding was influenced by the mother’s negative emotions and anxiety when they had more than one child to take care of [ 35 ]. Around 27% of women faced barriers to continuing with breastfeeding due to the pandemic lockdown [ 36 ]. Another study in the UK, from May 27 to June 2020, showed that 59% of women who delivered during lockdown exclusively breastfed / mixed-fed their infants compared to 39% who delivered before the COVID-19 pandemic [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic interfered with women obtaining postnatal in-person follow-up care and in-person breastfeeding support [ 54 ]. A study that compared the postnatal experiences of women who delivered before and during lockdown in the UK identified a decrease in feeding support from 57% to 40% [ 36 ]. Despite the pandemic situation, our study revealed that more than 50% of women received professional support (67% in the pooled sample), ranging from 86% in Thailand to 47% in South Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation